Analysis of E-Government Service Quality Using the E-GovQual Method (A Case Study at the Department of Communication and Information of Muara Enim Regency) - Meta Marta Lopa (Institute of Information Technology and Social Science (IITSS), 2025)
This study analyzes the quality of e-government services using the E-GovQual method at the Department of Communication and Information of Muara Enim Regency. Data collection was conducted through questionnaires, interviews, and observations with a total of 110 respondents. Validity test results indicated that all variable indicators exceeded the R-table value (R-count > 0.1562), confirming their validity. Reliability tests demonstrated consistent results for each variable: efficiency (0.581), trust (0.562), reliability (0.605), and citizen support (1.000). The findings reveal that the service quality of the Muara Enim Regency e-government website is generally satisfactory. However, several aspects, particularly user trust and citizen support, require improvement to enhance overall service effectiveness and user satisfaction.